2005
DOI: 10.1267/ahc.38.257
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrated Understanding of the Purkinje Fibers in the Heart: The Functional and Morphological Interconnection between the Purkinje Fibers and Ventricular Muscle

Abstract: Purkinje fibers are an essential element of the conduction system that provides for coordinated ventricular contraction of the heart. Although classic studies established structure and electrical activities of Purkinje fibers, an integrated understanding of the Purkinje-ventricular interconnection within the working heart remains to be had. In this review article we will briefly overview the gross anatomy and cytological characteristics of Purkinje fibers and their transition to the ventricular muscle, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…APD maxima remained localized to PMJs, in ischemic ( Figure 5 ) conditions with little change in APD compared to control. The preservation of PFs and their electrophysiological state during ischemic insult has previously been documented ( Tanaka et al, 2005 ; Ono et al, 2009 ). This phenomenon is thought to occur due to high glycogen levels permitting resistance to hypoxia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…APD maxima remained localized to PMJs, in ischemic ( Figure 5 ) conditions with little change in APD compared to control. The preservation of PFs and their electrophysiological state during ischemic insult has previously been documented ( Tanaka et al, 2005 ; Ono et al, 2009 ). This phenomenon is thought to occur due to high glycogen levels permitting resistance to hypoxia.…”
Section: Discussionmentioning
confidence: 91%
“…Although the resistance of PF toward ischemic insults due to a high metabolic reserve is well known ( Tanaka et al, 2005 ; Ono et al, 2009 ), as well as its potential to trigger arrhythmias ( Haissaguerre et al, 2002a ), the role of repolarization heterogeneity at the PMJ in providing an arrhythmogenic substrate during ischemia remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Given that cardiac performance is determined by electromechanical coordination of individual cardiomyocytes, visualization of the cellular aspects of intracellular Ca 2+ concentration ([Ca 2+ ] i ) dynamics in the heart is an important means of understanding cardiac pathophysiology [ 24 ]. So far, studies on [Ca 2+ ] i dynamics of cardiomyocytes have been well described not only under enzymatically isolated conditions [ 6 , 22 ] but also in working ventricles [ 1 , 9 13 , 18 , 20 , 23 25 ]. For example, we have reported cellular [Ca 2+ ] i dynamics in rat hearts imaged by using in situ rapid scanning confocal microscopy [ 9 12 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies on [Ca 2+ ] i dynamics of cardiomyocytes have been well described not only under enzymatically isolated conditions [ 6 , 22 ] but also in working ventricles [ 1 , 9 13 , 18 , 20 , 23 25 ]. For example, we have reported cellular [Ca 2+ ] i dynamics in rat hearts imaged by using in situ rapid scanning confocal microscopy [ 9 12 , 23 25 ]. These studies revealed that individual ventricular myocytes in the intact heart show spatiotemporally uniform [Ca 2+ ] i on beat-to-beat basis, whereas non-uniform [Ca 2+ ] i dynamics emerge in diseased or injured hearts, e.g., Ca 2+ waves that emerge under [Ca 2+ ] i overload.…”
Section: Introductionmentioning
confidence: 99%
“…Purkinje fibers play essential roles in impulse propagation to the ventricular myocardium, and their impaired function can become arrhythmogenic 41,42 . Under simultaneous recording on electrocardiogram, spatiotemporal changes in fluo3 fluorescence intensity were visualized in subendocardial regions of the right ventricular septum 43,44 . Purkinje fibers were distinguished from ventricular myocytes by their morphology in fluo 3‐fluorescence and later staining with acetylthiocholine iodide.…”
Section: Arrhythmogenic Disturbance Of Intracellular Calcium Ion Dynamentioning
confidence: 99%